Implementing digital resources for clinicians' and patients' varying needs. - Adams, Anne
This paper presents an overview of several evidence-based medicine and patient information studies conducted across the UK health services over a 4 year period, investigating clinicians', managers', and patients' perceptions of digital resources (primarily digital libraries) in hospitals, Primary Care Trusts, NHS Direct (patient call centre) and patient groups. In-depth interviews and focus groups are analysed using grounded theory methodologies and through content analysis used to produce quantitative finding. The perceived impacts of three different methods employed for delivering health informatics are presented. The findings highlight some generic issues relevant for health informatics in the UK health sector as well as some specific issues for medical digital libraries. This paper reviews in more detail the issues of medical technology implementation (traditional implementation, on the wards, and intermediaries within in communities). A breakdown of the clinicians' and patients' information journey (information initiation, facilitation and interpretation) is also presented with regard to medical digital libraries and online resources. Broad guidelines derived from these findings are provided for health-informatics deployment.
Keywords: Digital libraries; Evidence-based medicine; Patient information